The Perfusion Features of Recurrent Hepatocellular Carcinoma After Radiofrequency Ablation Using Contrast-Enhanced Ultrasound and Pathological Stemness Evaluation: Compared to Initial Tumors - Wu, Jin-Yu; Bai, Xiu-Mei; Wang, Hong; Xu, Qian; Wang, Song; Wu, Wei; Yan, Kun; Yang, Wei (Frontiers in Oncology, 2020)
Objective: To investigate the perfusion features of local recurrence in hepatocellular carcinoma (HCC) after radiofrequency ablation (RFA) with contrast-enhanced ultrasound (CEUS) and pathological correlation, as well as to compare with those of initial HCC. Methods: From 2010 to 2018, 42 patients with recurrent HCC after RFA were enrolled in this study. The initial HCC patients included 32 males and 10 females with an average age of 58.2 ± 8.1 years. The CEUS images for initial HCC lesions and local recurrence after RFA were compared. The perfusion features were analyzed, including enhancement time, process, boundary, morphology, washout time, washout degree, feeding vessels, and internal necrosis. H&E staining and CD133/EpCAM staining were performed with biopsy samples for the stemness study. Results: According to CEUS, 59.5% of initial HCC lesions had centripetal enhancement, and 61.9% of recurrent HCC lesions had homogeneous enhancement in the arterial phase (p < 0.001). A total of 73.8% of initial HCC lesions had well-defined margins at the peak, and 81.0% of recurrent HCC lesions had poorly defined margins (p < 0.001). A total of 78.6% of initial HCC lesions had regular morphology at the peak, and 83.3% of recurrent HCC lesions were irregular (p < 0.001). Feeding vessels were more frequently found in initial HCC lesion (71.4%) than in recurrent HCCs (38.1%, p = 0.002). In the late phase, 60% of initial HCCs had marked washout while 83.3% of recurrent HCC lesion had marked washout (p = 0.019). A total of 31.3% of the initial HCC lesions had internal necrosis areas while only 7.1% of recurrent HCC lesions had internal necrosis areas (p = 0.035). In tumors 3–5 cm in size, the washout time of recurrent HCCs was shorter than that of initial HCCs (50.3 ± 13.5 s vs. 75.6 ± 45.8 s, p = 0.013). Pathological staining showed that the tumor stem cell markers (CD133 and EpCAM) were both highly expressed in recurrent samples compared with initial tumor samples (CD133+: 19 vs. 5%, p = 0.002; EpCAM+:15 vs. 6%, p = 0.005). Conclusions: Recurrent HCC after RFA had more homogeneous enhancement with a poorly defined border, marked washout, and fewer less feeding vessels and inner necrosis areas compared to initial HCC. The stemness study also found upregulated stemness in recurrent HCC. These specific features might be related to the aggressive biological behavior of recurrent HCC.